Exploring the evolution of religious moderation leadership from the local to national level - Parhusip, Akdel (HTS teologiese studies, 2024)
Religious conflicts in Indonesia are prevalent, with endless debates, provocations, and strains among religious groups. Therefore, promoting moderation is crucial to alleviate, minimize, or even eradicate such tensions. Based on the country’s history related to the monarchy system, as well as the jumbled existence of political, religious, and social leaders in society, the role of a leader is significant. Unfortunately, Western, religious, and secular values of leadership have limited opportunities for implementation because of Indonesia’s heterogenous community. Therefore, this article argued that the native leadership knowledge of tona’as from Minahasa is a promising area to explore for religious moderation. To achieve the desired result, descriptive, analytical, and argumentative methods were employed. In conclusion, the responsibility, requirements, and praxis of a tona’as offers alternative insights into leadership in relation to religious moderation in Indonesia.Contribution: This article contributes the values of leadership model in Minahasa that could be a constructive contribution to the religious moderation in Indonesia. The knowledge and insight of tona’as as an original culture and tradition offers leadership philosophy that could bring harmony and peace.